Engaging ALS patients and caregivers (the ALS research ambassadors) to help design the REFINE-ALS biomarker study. Issue 1 (2nd January 2021) - Berry, James D.; Bedlack, Richard; Mathews, Debra; Agnese, Wendy; Apple, Stephen
Abstract: In the planning and design of the R adicava/E daravone F indings in Biomarke rs From A myotrophic L ateral S clerosis (REFINE-ALS) study, we sought to elicit feedback from patients with ALS and their caregivers to ensure that patient-centric issues would be addressed. Ten ALS Clinical Research Learning Institute (ALS-CRLI) Research Ambassadors participated in 2 meetings. They provided perspectives on patients' interest in the study, the schedule of study visits, and data sharing. The findings were used to help revise the study design, as appropriate. Key concerns identified were (1) the frequency of sample collections, (2) participant travel burden, (3) enrollment criteria, and (4) data reporting and sharing with participants. Several of the identified issues were promptly addressed. The number of visits was reduced, travel optimized, entry criteria clarified, and plans for sharing participants' data with them were codified. The feedback from the Ambassadors was substantive and resulted in constructive patient-centric changes to the study protocol.